2014
DOI: 10.1002/jor.22726
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C (APC) can increase bone anabolism via a protease-activated receptor (PAR)1/2 dependent mechanism

Abstract: Activated Protein C (APC) is an anticoagulant with strong cytoprotective properties that has been shown to promote wound healing. In this study APC was investigated for its potential orthopedic application using a Bone Morphogenetic Protein 2 (rhBMP-2) induced ectopic bone formation model. Local co-administration of 10 mg rhBMP-2 with 10 mg or 25 mg APC increased bone volume at 3 weeks by 32% (N.S.) and 74% (p < 0.01) compared to rhBMP-2 alone. This was associated with a significant increase in CD31þ and TRAPþ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…PAR family is composed of four members (PAR 1 , PAR 2 , PAR 3 , and PAR 4 ) distributed by several types of body cells. Because of a direct association with chronic inflammatory diseases such as arthritis and periodontitis, PAR 2 is the one most commonly studied 27 , 28 . In rats, Holzhausen et al 29 demonstrated that topical application of PAR 2 agonist induced significant ABL and gingival granulocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…PAR family is composed of four members (PAR 1 , PAR 2 , PAR 3 , and PAR 4 ) distributed by several types of body cells. Because of a direct association with chronic inflammatory diseases such as arthritis and periodontitis, PAR 2 is the one most commonly studied 27 , 28 . In rats, Holzhausen et al 29 demonstrated that topical application of PAR 2 agonist induced significant ABL and gingival granulocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether PAR2 protein is endogenously expressed in Neuro2a cells, RT-qPCR was performed using a PAR2-specific primer set (Fig. PAR2 mRNA levels in Neuro2a cells were similar to those of cells endogenously expressing PAR2, including 293T, HeLa, and MG63 [20][21][22]. PAR2 mRNA levels in Neuro2a cells were similar to those of cells endogenously expressing PAR2, including 293T, HeLa, and MG63 [20][21][22].…”
Section: Effects Of Rgs Proteins On Par2/ga I/o -Mediated Signalingmentioning
confidence: 99%
“…Interestingly, EPCR expression in the BM is not limited to LT-HSCs, as preosteoblasts and osteoblasts also functionally express EPCR. 131,132 EPCR expression by osteoblasts might also participate in bone turnover, as aPC stimulates osteoblast proliferation via EPCR 132 and administration of aPC together with bone morphogenetic protein 2 in mice induced ectopic bone formation with higher rates of osteoclast differentiation and vascularization, all implicated in bone-remodeling processes. 131 Further evidence linking hemostatic regulation with bone physiology demonstrated that long-term oral anticoagulant therapy in children is associated with osteopenia and a risk of future development of osteoporosis, 133 possibly indicating the need for balanced production of anticoagulant factors and normal bone turnover.…”
Section: Bone Remodeling and Hemostasis Cross Talk Modulates Hsc Mainmentioning
confidence: 99%